How Did I Feel Before Becoming Diabetes Resilience? A Qualitative Study in Adult Type 2 Diabetes Mellitus - Hidayat Arifin; Kusnanto Kusnanto; Ika Yuni Widyawati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: Diabetes resilience is a condition where people with diabetes can accept their incurable disease as well. It is characterized by regular blood sugar, a diet-controlled, active, and not stressful. However, various kinds of feelings must be passed to become diabetes resilience. The study aimed to know what adult type 2 diabetes mellitus (T2DM) felt before becoming resilient. Methods: A qualitative phenomenology design was conducted to observe the experience of adult T2DM before becoming resilient. The total participants were ten T2DM patients obtained through snowball sampling. The data collection was conducted through in-depth interviews with interview guidelines and analyzed using qualitative thematic analysis. Results: The results of the study found two major themes namely psychological response and diet. Participants felt quite severe stress when diagnosed with diabetes mellitus and felt difficulty when undergoing diabetes mellitus treatment. In addition, changes in diet are also felt very difficult by participants in undergoing a diabetes mellitus diet. Conclusions: Psychological responses and diet are the hard parts felt by the participants. Increasing understanding, support, and acceptance can be one strategy to increase diabetes resilience in participants.